Upaya Pencegahan Diare Berulang Pada Anak Usia Toodler - Rahmad, Hussin Nur, Endang Zulaicha Susilaningsih S.Kp, M.Kep (2017)
Diarrheal disease is still a public health roblem,especially in children. Less than 80% of deaths related to diarrhea occurred in 2 years of step in life. In Indonesia morbidity and mortality is still high. Diarrhea always called chronic or recurrent diarrhea. Recurrent diarrhea in children can cause nutritional deficiencies, dehydration and death. The objective of study is to describe the common goalofrevention recurrent diarrhea in children under five. The specific objective to analyze the studies on the prevention of recurrent diarrhea in children under five, analyzed interventions in the prevention of diarrhea in children under five and analyze measures for the prevention of recurrent diarrhea in children under five, analyze the environment and behavior before and after the do ementation. The research methods are the writer uses descriptive method with case studies for 3 days, starting on 11 February 2017 to 13 February 2017, the health center in Bulu village Sukoharjo. The results of research by the author are the prevention of recurrent diarrhea in children. Intervention by the author include: observation of mothers' knowledge of diarrhea, do health education about how to clean and healthy lifestyle, health education on how to wash hands properly with soap and health education how to make soybean porridge. Conclusion: to treat recurrent diarrhea in children, nducted health education measures on how to prevent diarrhea, with a clean and healthy living to parents, one of whose contents are taught hand-washing with soap. Cooperation is needed among parents, clients, and health care workers for the success of the nursing process. After 3 days of nursing interventions for the children will not be repeated diarrhea and the parents can implement healthy lifestyle and clean, so that interventions can be maintained.